Rapid Seedless Synthesis of Gold Nanoplates with Microscaled Edge Length in a High Yield and Their Application in SERS - Chen, Sheng; Xu, Pengyu; Li, Yue; Xue, Junfei; Han, Song; Ou, Weihui; Li, Li; Ni, Weihai (Nano-Micro Letters, 2016)
We report a facile and reproducible approach toward rapid seedless synthesis of single crystalline gold nanoplates with edge length on the order of microns. The reaction is carried out by reducing gold ions with ascorbic acid in the presence of cetyltrimethylammonium bromide (CTAB). Reaction temperature and molar ratio of CTAB/Au are critical for the formation of gold nanoplates in a high yield, which are, respectively, optimized to be 85 °C and 6. The highest yield that can be achieved is 60 % at the optimized condition. The synthesis to achieve the microscaled gold nanoplates can be finished in less than 1 h under proper reaction conditions. Therefore, the reported synthesis approach is a time- and cost-effective one. The gold nanoplates were further employed as the surface-enhanced Raman scattering substrates and investigated individually. Interestingly, only those adsorbed with gold nanoparticles exhibit pronounced Raman signals of probe molecules, where a maximum enhancement factor of 1.7 × 107 was obtained. The obtained Raman enhancement can be ascribed to the plasmon coupling between the gold nanoplate and the nanoparticle adsorbed onto it.